IMPLEMENTASI ALGORITMA FUZZY C-MEANS PADA PENGELOMPOKAN SISWA PKL: (Studi Kasus : SMK MUTIARA SALAWU) - Uro Abdulrohim; Siti Adawiah; Herna Gunawan (LPPM STMIK BANDUNG, 2020)
Mutiara Salawu Vocational School also participates in government programs to carry out PKL. However, PKL at SMK Mutiara Salawu is different as it does with other SMKs, it does not mean that there is nothing but rarely SMKs that direct their students to PKL in a place that has been determined based on the specified report cards. Because Salawu Mutiara Vocational School places PKL students who have been determined by the school, it is necessary to have a supportive system for classifying students based on the specified report cards. Implementation of Fuzzy C-Means algorithm to classify street vendors students based on their respective report cards. The results of this implementation are in the form of software that can be used as a tool to help schools classify PKI class XI students based on report cards to help prepare PKL placement as desired by the street vendors chosen by the school using the Fuzzy C- algorithm Means Based on the test results, the grouping of street vendors students can be concluded that this grouping can produce output in accordance with what users expect. Keywords: Algorithms, Fuzzy C-Means, Grouping students